Analysis of retinal and choroidal characteristics in patients with early diabetic retinopathy using WSS-OCTA - Qi, Zhihao; Si, Yuanyuan; Feng, Feng; Zhu, Jing; Yang, Xuepeng; Wang, Wenjuan; Zhang, Yuting; Cui, Yan (Frontiers in Endocrinology, 2023)
The purpose of this study was to evaluate the changes in fundus microcirculation in non-diabetic retinopathy (NDR) and mild non-proliferative diabetic retinopathy (NPDR) in patients with type 2 diabetic mellitus (T2DM) using widefield swept-source optical coherence tomography angiography (WSS-OCTA), and to investigate the correlation with laboratory indices of T2DM. Eighty nine, 58 and 28 eyes were included in the NDR, NPDR and Control groups, respectively, were enrolled in this study. The 12mm×12mm fundus images obtained by WSS-OCTA were divided into 9 regions (supratemporal, ST; temporal, T; inferotemporal, IT; superior, S; central macular area, C; inferior, I; supranasal, SN; nasal, N; inferonasal, IN) to evaluate changes in vessel density (VD) of the superficial capillary plexus (SCP), deep capillary plexus (DCP), choriocapillaris, and mid-large choroidal vessel (MLCV), as well as changes in inner retinal thickness (IRT), outer retinal thickness (ORT), and choroidal thickness (CT). Compared with control group, MLCV VD (I, N, IN) was significantly decreased in NDR group, SCP VD (IT, C, I) and DCP VD (T, IT, I) were significantly decreased in NPDR group. In NPDR group, DCP VD (IT) was significantly decreased compared with that in NDR group. Compared with control group, CT (ST, T, IT, S, SN, IN) was significantly declined in NDR group, and IRT (ST, IT) and ORT (ST, N) were significantly increased in NPDR group. In NPDR group, IRT (ST) and ORT (T, S) were significantly increased compared with NDR group. Correlation analysis showed that age, body mass index, fasting blood glucose, fasting insulin, fasting C-peptide, and estimated glomerular filtration rate in T2DM patients were statistically correlated with retinal and choroidal thickness/VD. Structural and blood flow changes in the choroid occur before the onset of DR and precede changes in the retinal microcirculation, and MLCV thickness/VD is a more sensitive imaging biomarker for the clinical detection of DR. WSS-OCTA enables large-scale non-invasive visual screening and follow-up of the retinal and choroidal vasculature in DR patients, providing a new strategy for the prevention and monitoring of DR in patients with T2DM.